Understanding quality of care and analyzing different strategies to assure and improve it. (13th November 2019) - Busse, R; Panteli, D; Quentin, W
Abstract: Assessing and improving quality of care presupposes an understanding of what it does and does not entail. Different definitions often specify relatively long lists of various attributes that they recognize as part of quality. Effectiveness, patient safety, and responsiveness/patient-centeredness seem to have become universally accepted as core dimensions of quality of care. The inclusion of a list of additional elements is confusing and often blurs the line between quality of care and overall health system performance. This presentation provides an in-depth look at this interplay, recognizing that the definition of quality changes depending on the level at which it is assessed. At the level of health services, there seems to be an emerging consensus that quality of care is the degree to which health services for individuals and populations are effective, safe, and people-centered. On the other hand, a health care system as a whole is of high quality when it achieves the overall goals of improved health, responsiveness, financial protection, and efficiency; here, there seems to be an international trend towards using the term health system performance. The workshop looks at different strategies to assure or improve the quality of health care. To understand, analyze, compare and ultimately prioritize or align different quality strategies, this presentation will introduce a comprehensive framework, which includes the following lenses: i) the three core dimensions of quality: safety, effectiveness, and patient-centeredness; ii) the four functions of health care: primary prevention, acute care, chronic care, and palliative care; iii) the three main activities of quality strategies: setting standards, monitoring, and assuring improvements; iv) Donabedian's triad: structures, processes, and outcomes; v) the five main targets of quality strategies: health professionals, technologies, provider organizations, patients, and payers.